1989
DOI: 10.1248/cpb.37.2481
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical changes of medicinals in mixtures with adsorbents in the solid state. II. Application of reduced pressure treatment for the improvement of dissolution of flufenamic acid.

Abstract: Flufenamic acid (FFA) was mixed with magnesium aluminum silicate (MAS) and stored at 60 degrees C at a reduced pressure of about 2.5 mmHg. After storage, when its concentration was not more than 20%, FFA was observed by X-ray diffraction and polarizing microscopy to be amorphous. The dissolution of FFA was thus enhanced in comparison with that of a freshly prepared mixture. Furthermore, the dissolution curves showed a typical supersaturation pattern, and the supersaturation state continued longer, the higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In recent years, porous adsorbents have captured the attention of some scientists, leading them to investigate their possible applications in drug delivery. The main investigational application of these porous adsorbents was their role in enhancing the solubility of poorly water soluble drugs 1–10. Poor aqueous solubility is one of the main reasons many drug candidates cannot reach the market in spite of exhibiting potential pharmacodynamic activity 11.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, porous adsorbents have captured the attention of some scientists, leading them to investigate their possible applications in drug delivery. The main investigational application of these porous adsorbents was their role in enhancing the solubility of poorly water soluble drugs 1–10. Poor aqueous solubility is one of the main reasons many drug candidates cannot reach the market in spite of exhibiting potential pharmacodynamic activity 11.…”
Section: Introductionmentioning
confidence: 99%
“…Other analytical methods should be considered in such a situation. There have been increased interests in using porous adsorbents to improve the dissolution rate of poorly water-soluble drugs either by simple mixing or solid dispersion, [20][21][22] and DSC has been routinely used as a qualitative method to study such phase transformation in crystalline drugs/porous adsorbents mixtures. [23][24][25] Here, we report the development of quantitative methods using both DSC and XRPD to measure the crystallinity of indomethacin (IMC) in mixtures with the adsorbent, silica gel (SG).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of drug loading and degree of amorphization is influenced by various factors like time and intensity of mixing, reduced pressure, humidity, and silanol content. In most of the earlier studies, the extent of amorphization is found to be proportional to time and intensity of mixing (Konno and Kinuno 1989;Konno et al 1986). However, contradictory observations were made with a study conducted by Pan et al (2008) where the amorphization of indomethacin was found to be independent of both parameters, which is explained by the low glass transition temperature (T g ) of the drug.…”
Section: Co-grinding/co-milling Methodsmentioning
confidence: 88%